Oxidized low‐density lipoprotein suppresses mouse granulosa cell differentiation through disruption of the hypoxia‐inducible factor 1 pathway. Issue 12 (18th December 2017) - Chen, Xiaoliang; Liu, Yanhong; Shan, Yanhong; Jin, Xingyi; Shi, Qingyang; Jia, Chunshu
Abstract : Obesity predisposes women to reproductive disorders. One symptom of obesity in women is higher levels of oxidized Low‐density lipoprotein (oxLDL) in serum and preovulatory follicles. The present study was designed to test the hypothesis that oxLDL might impair follicle differentiation and luteinization. Given that Hypoxia‐inducible factor 1 (HIF1) plays crucial roles in supporting follicle differentiation and luteinization in mammals, we focused on oxLDL‐mediated events that may affect the HIF1 pathway. We report that exposure to oxLDL diminished the expression of HIF1α and its target genes and suppressed the differentiation of mouse luteinized granulosa cells following induction by human Chorionic gonadotophin (hCG) under hypoxic conditions (1% oxygen). Significantly, the proteasome inhibitor MG‐132 prevented this oxLDL‐attenuation differentiation phenotype by blocking HIF1α degradation. Together, these findings suggest that suppression of granulosa cell differentiation by oxLDL, via HIF1α down‐regulation, may contribute the negative effects of obesity on female fertility.